The Therapeutic Effect of Prodigiosin Pigment Produced From Serratia Marsenies Bacteria on Injure Wounds In Rats - Ahmed thabetjabar,; Shaymaa mohammedtaher,; Fatima nashwannadheer,; Ahmed saadihossein,; Mohammed F. Al Marjani,; Raghad Akram aziz, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Serratia marcescens isolates were collected from urinary tract infections, and diagnosed phenotypically and biochemical tests. The diagnosis of the isolates was confirmed using Vitik2 device. To confirm the strain producing the pigment, the bacterial strains were examined using the PCR technique. The pigment was extracted using the organic solvent methanol, then confirmed using the TLC technique. Then the dry pigment was collected also absorbance was measure in spectrophotometer. optimum conditions for pigment production were tested, which gave the highest production on B. H. I. media with a mixture of fatty acids and sucrose added, at a temperature of 28 C for a moving incubation while (150 / min) for 72 hours. At a pH of 7. Tests of the pigment inhibitory effectiveness against pathogenic bacteria in the laboratory, and the pigment therapeutic effectiveness against wounds created in the body of the living organism, showed positive results compared to the antibiotics used in the experiments.